Dissecting the causal links between gut microbiome, immune traits and polyp using genetic evidence - Zhou, Cheng; Ye, Xiaofeng; Liu, Zhinuo; Liu, Tong; Li, Shanzheng; Yang, Jinqiu; Wei, Jingjing; Yu, Peng; Jia, Ran; Zhao, Wenxia (Frontiers in Immunology, 2024)
This study aims to use Mendelian randomization (MR) to investigate the causal relationship between gut microbiota and 4 types of polyps (nasal, gallbladder, colon, and gastric polyps), as well as to analyze the mediating role of immune traits. This study utilized large-scale GWAS meta-analyses of gut microbiota (MiBioGen Consortium), 731 immune traits, and 4 types of polyps (one from the FinnGen Consortium and three from the NBDC Human Database). Univariate MR with the inverse variance weighted (IVW) estimation method was employed as the primary analytical approach. A two-step MR analysis was performed to identify potential mediating immune traits. Additionally, multivariable MR approach based on Bayesian model averaging (MR-BMA) was employed to further prioritize gut microbiota and immune traits associated with polyp development. Based on IVW method in univariate MR analysis, we identified 39 gut microbial taxa and 135 immune traits significantly causally associated with at least one type of polyp. For nasal polyps, 13 microbial taxa and 61 immune traits were causally associated. After false discovery rate (FDR) correction, CD3 on Central Memory CD8+ T cells and CD3 on CD4 regulatory T cells remained significant. MR-BMA identified 4 gut microbial taxa and 4 immune traits as high priority. For gallbladder polyps, 9 microbial taxa and 30 immune traits were causally associated. MR-BMA identified 8 microbial taxa and 6 immune traits as higher importance. For colon polyps, 6 microbial taxa and 21 immune traits were causally associated. MR-BMA identified 4 microbial taxa and 3 immune traits as higher importance. For gastric polyps, 12 microbial taxa and 33 immune traits were causally associated. Actinobacteria remained significant after FDR correction, and MR-BMA identified 7 gut microbial taxa and 6 immune traits as high priority. We identified 16 causal pathways with mediator directions consistent with the direction of gut microbiome-polyp association. Of these, 6 pathways were associated with the mechanism of nasal polyps, 1 with gallbladder polyps, 2 with colon polyps, and 7 with gastric polyps. Our findings shed light on the causal relationships between gut microbiota, immune traits, and polyp development, underscoring the crucial roles of gut microbiota and immune status in polypogenesis.